Comparative Learning Profiles of Children with Autism Spectrum Disorder Across Inclusive and Special School Settings - Astiti Tenriawaru Ahmad; Nurfajriyanti Rasyid; Amirah Aminanty Agussalim (Indonesian Journal of Educational Studies, 2026)
Abstract. The learning profiles of children with Autism Spectrum Disorder are highly heterogeneous and cannot be understood through a generic approach without in-depth contextual analysis. This study aimed to compare the learning profiles of two children with ASD across two educational settings: an inclusive school and a special school. A case study was conducted involving MRS (7 years and 2 months old, TKIT Darul Fikri Makassar) and RH (7 years old, SLBN 1 Wajo). Data were collected through structured and semi-structured interviews with parents and special education teachers, as well as direct classroom observations. Qualitative analysis was guided by the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition framework, Sensory Integration Theory, Executive Function Theory, and the neurodiversity perspective. The findings revealed significant differences in attention, sensory processing, language, and social functioning between the two participants, despite both having an ASD diagnosis. MRS demonstrated attentional regulation deficits alongside notable academic strengths, whereas RH exhibited difficulties in processing verbal instructions, with echolalia as a dominant characteristic. The educational setting appeared to influence the manifestation of both learning challenges and strengths in children with ASD. These findings underscore the importance of designing educational services based on each child's individual learning profile rather than relying solely on diagnostic categories. Keywords: Autism Spectrum Disorder, learning profile, comparative analysis, inclusive school, special school.